Graph-Based Representations in Pattern Recognition 8th IAPR-TC-15 International Workshop, GbRPR 2011, Münster, Germany, May 18-20, 2011, Proceedings - Jiang, Xiaoyi.; Jiang, Xiaoyi.; Ferrer, Miquel.; Ferrer, Miquel.; Torsello, Andrea.; Torsello, Andrea. (Image Processing, Computer Vision, Pattern Recognition, and Graphics ;, 2011)
This book constitutes the refereed proceedings of the 8th IAPR-TC-15 International Workshop on Graph-Based Representations in Pattern Recognition, GbRPR 2011, held in Münster, Germany, in May 2011. The 34 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on graph-based representation and characterization, graph matching, classification, and querying, graph-based learning, graph-based segmentation, and applications.